The Relationship of course choices of high school seniors to their parents' educational attainments, occupational levels, and course choices for their children - Fernandez, Belen Valdez 1936- (s.n.], 1967)
This study examined the relationships of the course choices of seniors to their parents' educational attainment, occupation and their parents course choices for their children. The respondents to this investigation are from the academically successful and unsuccessful seniors in selected high schools in Quezon City in the school years 1965-1966 and 1966-1967.